Regional trends in the use of steroids and favipiravir for COVID-19 treatment - Yusuke Asai; Shinya Tsuzuki; Nobuaki Matsunaga; Norio Ohmagari (Elsevier, 2023)
Background: Infectious diseases are treated based on clinical guidelines, which usually require a large amount of data and time to formulate. Therefore, various treatments are tried and used in the early stages of epidemics of emerging and reemerging infectious diseases. In this study, we focused on two drugs for coronavirus disease 2019 (COVID-19) treatment, i.e., steroids and favipiravir, and analyzed the changes in treatment trends by region. Methods: This was a retrospective study of cases from the COVID-19 Registry Japan. The proportion of patients who received steroids and favipiravir was calculated on a monthly and pandemic wave basis, and the trend of drug administration by region was estimated using logistic curves. Results: The effect of wave on steroid administration was as high as 2.75 [2.60, 2.90], indicating a rapid increase in the proportion of steroid administration. The odds ratios for Hokuriku and Hokkaido were 0.49 [0.35, 0.68] and 0.55 [0.43, 0.71], respectively, indicating that steroids were less likely administered in these regions. For favipiravir, the effect of timing was 0.43 [0.41, 0.46], denoting a decreasing trend. On the other hand, the odds ratio was very high in some regions, such as Hokkaido (6.66 [5.24, 8.48]), indicating that the administration trend varied by region. Conclusions: The increase in the proportion of steroid use showed the same trend nationwide, although the rate of increase differed, confirming that the use of drugs with proven efficacy was spreading rapidly and that effective treatment was available nationwide. However, the results suggest that drugs such as favipiravir, which were initially expected to be effective, may continue to be administered. Registry studies include larger populations than clinical trials and enable real-time monitoring of medication status and trends. Further use of registry studies for treatment standardization is expected in the future.